Engineering bone from fat: a review of the in vivo mechanisms of adipose derived stem cell-mediated bone regeneration. (9th August 2021) - Horenberg, Allison L; Rindone, Alexandra N; Grayson, Warren L
Abstract: Adipose-derived stromal/stem cells (ASCs) have considerable potential to promote bone regeneration due to their ease of isolation, abundance, and osteogenic capacity. However, despite two decades of research, studies of the precise mechanisms underlying their in vivo osteo-regenerative capacity remain contradictory. Specifically, there are multiple reports that suggest either a direct mechanism (i.e. ASCs directly differentiate into osteoblasts and lay done new bone matrix) or an indirect mechanism (i.e. ASCs stimulate endogenous cells via their secretory profiles) of bone regeneration. To address this discrepancy we critically reviewed studies utilizing ASCs for in vivo bone regeneration and employed methods to track cell fate. We evaluated the rigor of individual studies by examining the specific defect and animal models employed, cell sorting or pretreatment methods, and quantitative assessments of cell dosing and cell survival/distribution data to determine the strength of their claims. There is robust evidence to support both a direct differentiation of ASCs and indirect signaling based on secreted factors: osteogenic/angiogenic, immunomodulatory, or extracellular matrix factors, suggesting that a combination of factors underlie the pro-regenerative capacity of ASCs. However, there remains significant knowledge gaps regarding the precise efficiency of ASC engraftment following transplantation, the types of spatiotemporal interactions that occur between ASCs and host cells during the different stages of healing, and the contributions of osteoclasts, nerves, and immune cells to ASC-mediated regeneration. Emerging technologies will enable further elucidation of the specific mechanisms of action of ASCs in bone regeneration.